PROFITABILITAS, UKURAN PERUSAHAAN, LEVERAGE TERHADAP TAX AVOIDANCE - Tarisyah Cahyatie; Mulia Rahmah (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2023)
This research aims to analyze the influence of profitability on tax avoidance, company size on tax avoidance, leverage on tax avoidance, as well as the influence of profitability, company size and leverage on tax avoidance simultaneously. The population in this study are registered manufacturing companies in the consumer goods industry sector, sub-sector of the food and beverage industry on the Indonesian Stock Exchange in 2017-2021. The sampling technique uses a purposive sampling method by considering certain criteria, resulting in a sample of 75 data samples. The data analysis method uses descriptive statistical analysis and multiple regression analysis, processed using SPSS version 26. The results of the regression test show that the profitability variable and the leverage variable have a significant influence on tax avoidance, while company size does not have a significant influence on tax avoidance. Simultaneous statistical test results show that the variables profitability, company size and leverage together have a significant influence on tax avoidance. It is hoped that future research can use more company samples and from different sectors on the Indonesia Stock Exchange using the IDX-IC classification, further research can increase the research period so that it can generalize more.